التأثير الدلالي لاختلاف عامل الحال من حيث الصنعة النحوية في القرآن الكريم(دراسة نحوية دلالية): The Semantic Effect of diversity of Agents by the status in terms of Grammatical Structure in the Holy Qur’an(A Syntactic Semantic Study) - Dr. Madiha Sadiq,; Dr. Muhammad Bashir, (MEI, 2023)
It is self-evident that the utmost honorable, discourse and eloquent texts of all is the Allah’s almighty book, revealed on most eminent Prophet for the guidance of the whole mankind. The Holy Qur’an verses demand an insight and careful consideration in order to reveal its hidden treasures and to illuminate human life. This article endeavors to respond to this demand, as it explores the diversity of Agents by the status in terms of Grammatical Structure and its profound impact on the meaning of the Holy Text. It highlights the importance of this Syntactical issue in perspicacious understanding of the Qur’anic styles, diverse meanings and eloquent concepts. This article comprises of Preface and three sections. The Preface contains a brief theoretical study about the Agent by the Status, the first section is about the diversity between two Agents by the Status in terms of Grammatical Structure of singular case. The second section is about the diversity between two agents by the Status in terms of Grammatical Structure of the sentence case. The third section deals the diversity of Agents by the Status in terms of Grammatical Structure of the semi-sentence case.